Fifteen ways to fight pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
IPM for smallholders. A researcher s case book from Malawi By J Lawson-McDowall, S Abeyasekera, B Mwale et al. Published by Natural Resources Institute (NRI), UK, 2001. 89 pp. ISBN 0 85954 526 1 GBP 15 Euro 24.35 Please quote PSTC33